(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The aim of this study was to determine the antibiotic resistance rates of H. pylori and the eradication outcomes of first-line treatment regimens based on susceptibility testing in children at Children’s Hospital 2 from January to December 2024. Methods: A retrospective descriptive case series study. Results: From January to December 2024, 136 patients were included. The mean age was 9,6 ± 2,4 years, with the 6–10 years age group being the largest (46,3%). Females accounted for 53%. Family history of H. pylori infection was reported in 57.4%, indicating familial transmission risk. Nutritional status showed 53% normal, 29.4% underweight and 17,6% overweight, obese. Abdominal pain was the predominant symptom (93.4%). Upper gastrointestinal endoscopy revealed inflammatory lesions in 81% of cases and ulcerative lesions in 26,5%. Resistance rates were high for clarithromycin (100%), amoxicillin (77.9%) and metronidazole (69.8%), while resistance to levofloxacin and tetracycline was lower (31,6% and 2,2%, respectively). The overall eradication rate was 63.9%, about 77,9% of patients showed symptom improvement after treatment. There was a significant association between symptom improvement and successful eradication (OR = 5.31; p < 0,001). Conclusion: This study showed a relatively high resistance rate of H. pylori to clarithromycin and amoxicillin. Therefore, choosing antibiotics based on susceptibility testing and personalizing treatment is important to improve eradication rates.